ANALISIS TERHADAP PUTUSAN YANG TERDAPAT PEMERIKSAAN SAKSI SEDARAH TERHADAP PERKARA NOMOR 08/PID.PRAP/2017/PN. PBR DENGAN PERKARA NOMOR 24/PID.PRAP/2017/PN.PBR (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The process of proof in a trial that is passed through a process of examining evidence of witness testimony. Proving is considered as the main way to resolve each case in a trial. In the process of substantiating witness testimonies, witnesses that have had blood relations provided witness statements. In the case of Case Number 24 / PID.PRAP / 2017 / PN.BR where the witness gave the witness' statement and in the trial process the witness was under oath. While in case case Number 08 / PID.PRAP / 2017 / PN.BR the witness who gave the witness statement also had blood relations but was not under oath when giving witness statements.In this study the authors used Normative research. Normative research in the form of library law research. In this type of legal research, law is often conceptualized as what is written in: legislation or law conceptualized as a rule or norm which is a benchmark of human behavior that is considered appropriate.From the results of the research that the author did, it can be concluded that, firstly, the strength of evidence in the form of blood witness testimonies in the process of evidence based on the Criminal Procedure Code, Evidence is an important element in substantiating trials, because judges use it as a material for consideration in deciding cases. A witness who has certain family ties to the defendant cannot swear an oath. Unless they want it, and their will is agreed to explicitly by public prosecutors and defendants. secondly the validity of blood witness testimony in the Criminal Justice System, Normatively: blood witness testimony has been legitimized by Article 168 of the Criminal Procedure CodeKeywords: oath-witness examination